59‐1: Invited Paper: Scaling Down of OLED Pixels Enabled by Photolithography. Issue 1 (28th June 2022) - Ke, Tung-Huei; Singh, Arjun; Tankut, Firat; Vandenplas, Erwin; Ameys, Marc; Malinowski, Pawel; Genoe, Jan; Heremans, Paul
Abstract : This paper discusses the advantages of OLEDs in pixel scaling and the novel device structures enabled by photolithography. We show the pixel layouts that can be realized by photolithographic patterning, i.e., delta and color strip pixel layout with high pixel density. Further integration of OPD next to an OLED pixel is discussed. Finally, we show the OLED performance after three times OLED patterning steps, which is crucial for the full‐color OLED display realized by photolithography patterning processes. The results suggest that the photolithography patterning process could be a powerful method to further enhance the AMOLED display performance.